Cost engineering approach to project evaluation conception to obsolescence - Templeton, Robert; Ponder, Thomas (My University, 1980)
This seminar will provide both owners and contractors with a broad, but pertinent introduction to the critical success factors involved in project evaluation.
Keywords: project; maintenance; energy; industrial; cost; evaluation